Requirements engineering process improvement and related models - Solemon B.; Sahibuddin S.; Ghani A.A.A. (IGI Global, 2023)
Requirements Engineering (RE) is a key discipline in software development, and several standards and models are available to help assess and improve RE processes. However, different standards and models can also help achieve different improvement goals. Thus, organizations are challenged to select these standards and models to best suit their specific context and available resources. This chapter presents a review of selected RE-specific and generic process improvement models that are available in the public domain. The review aims to provide preliminary information that might be needed by organizations in selecting these models. The chapter begins with analyses of how RE maturity is addressed in the Capability Maturity Model Integration (CMMI) for Development. Then, it describes the principal characteristics of, and the assessment and improvement framework applied in four RE-specific process assessment and improvement models: the Requirements Engineering Good Practice Guide (REGPG), the Requirements Engineering Process Maturity(REPM), the Requirements Capability Maturity Model (R-CMM), and the Market-Driven Requirements Engineering Process Model (MDREPM). This chapter also examines the utility and lesson learned of these models. 2014, IGI Global.